SOCIO-ECONOMIC IMPACTS OF EPIDEMIC DISEASES OF FARM ANIMALS - Zawojska, Aldona; Siudek, Tomasz (Acta Scientiarum Polonorum. Oeconomia, 2018)
Based on desk research and literature review, the paper identifies the effects of farm animal disease outbreaks from the economic perspective. It provides a brief overview of broad impacts of trans-boundary animal diseases such as Bovine Spongiform Encephalopathy (BSE) and Foot and Mouth Disease (FMD) on the economy and society. It also presents a synthetic summary of the results of several studies dealing with the assessment and estimation of the costs of BSE and FMD epidemics in selected countries. The two epidemics were costly, both in monetary and non-monetary terms. Assessed direct and indirect economic losses were equivalent to several billion US dollars or euro in the countries under consideration. The economies depending on the export of live animals and meat products (e.g. the UK and Canada) were particularly affected. The economic welfare losses from hypothetical FMD outbreak in the USA could exceed a hundred billion US dollars. From the political perspective, government-run policies aimed at controlling and eradicating dangerous animal diseases seem to find the justification primarily in economic rationality or international competitiveness arguments.